Our lost Constitution : the willful subversion of America's founding document - Lee, Mike, frey50 (New York Sentinel, 2015)
Lee tells the dramatic, little-known stories behind six of the Constitution's most indispensable provisions. He shows their rise and fall, and he makes vividly clear how nearly every abuse of federal power today is rooted in neglect of this lost constitution.
Introduction -- Ducking and dodging the Constitution -- The lost clauses. The compromise that saved the Constitutional Convention... and that should have saved us from Obamacare: the forgotten origination clause ; From Congress to a king: the forgotten legislative powers clause ; The Supreme Court's Klansman: the forgotten establishment clause ; Liberty: "A reality or a shadow"?: the forgotten fourth amendment ; "But structure means liberty": the forgotten tenth amendment and the inflated commerce clause -- Reclaiming the lost clauses. Reclaiming the Constitution through the courts ; Reclaiming the Constitution through legislation ; Reclaiming the Constitution through the power of the purse ; What you can do to reclaim the Constitution.
Keywords: United States; Constitutional law -- United States; Constitutional history -- United States; United States -- Politics and government